Quantitative Intracellular pH Determinations in Single Live Mammalian Spermatozoa Using the Ratiometric Dye SNARF-5F - Chávez, Julio C.; Darszon, Alberto; Treviño, Claudia L.; Nishigaki, Takuya (Frontiers in Cell and Developmental Biology, 2020)
Intracellular pH (pHi) plays a crucial role in mammalian sperm physiology. However, it is a challenging task to acquire quantitative single sperm pHi images due to their small size and beating flagella. In this study, we established a robust pHi imaging system using the dual-emission ratiometric pH indicator, SNARF-5F. Simultaneous good signal/noise ratio fluorescence signals were obtained exciting with a green high-power LED (532 nm) and acquiring with an EM-CCD camera through an image splitter with two band-pass filters (550-600 nm, channel 1; 630-650 nm, channel 2). After in vivo calibration, we established an imaging system that allows determination of absolute pHi values in spermatozoa, minimizing cell movement artifacts. Using this system, we determined that bicarbonate increases non-capacitated human pHi with slower kinetics than in mouse spermatozoa. This difference suggests that distinct ionic transporters might be involved in the bicarbonate influx into human and mouse spermatozoa. Alternatively, pHi regulation downstream bicarbonate influx into spermatozoa could be different between the two species.